Genre - Neale Stephen (BFI Publishing, 1980)
Foreword, Head or Heart? The Political Use of Body Metaphors in the Middle Ages, The Art of Pulling Teeth in the Seventeenth and Nineteenth Centuries: From Public Martyrdom to Private Nightmare and Political Struggle, ''Amor Vaneris - Vel Dulcedo Appeletur'', Subtle Bodies, Semen and Blood: Some Ancient Theories Concerning Their Genesis and Relationship, Upanishad of the Embryo, Bodily Images in Melanesia: Cultural Substances and Natural Metaphors, Older Women and Stout-Hearted Women and Women of Substance, Personal Status and Sexual Practice in the Roman Empire, The Social Evil and the Solitary Vice and Pouring Sea, The Bio-Economics of Our Mutual Friend, The Meaning of Sacrifice, The Sacrificial Body of the King, The Emperor-God's Other Body, The Body-of-Power and Incarnation at Port Royal and in Pascal or of the Figurability of the Political Absolute, Mapping the Body, A Repertory of Body History.